Parallel synthesis and biological evolution of quinic acid derivatives as immuno-suppressing agents against T-cell receptors1. Issue 63 (10th July 2015) - Huang, Chih-Yu; Chen, Li-Hsun; Huang, Hsuan-Yu; Kao, Feng-Sheng; Lee, Yun-Ta; Selvaraju, Manikandan; Sun, Chung-Ming; Chen, Hueih-Min
<x xml:space="preserve">Abstract</x> A parallel synthesis of quinic acid derivatives is explored and their biological evolution against T-cells is studied.